2020
DOI: 10.3390/ma13092078
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Anodes for Microbial Fuel Cells: An Overview

Abstract: The recycling and treatment of wastewater using microbial fuel cells (MFCs) has been attracting significant attention as a way to control energy crises and water pollution simultaneously. Despite all efforts, MFCs are unable to produce high energy or efficiently treat pollutants due to several issues, one being the anode’s material. The anode is one of the most important parts of an MFC. Recently, different types of anode materials have been developed to improve the removal rate of pollutants and the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 176 publications
(120 reference statements)
2
65
0
7
Order By: Relevance
“…Bacillus subtilis is an aerobic, Gram-positive, spore forming, and rod-shaped bacterium commonly found in soil, water, and plants. It can produce various metabolites and has great potential in industrial applications [85][86][87][88]. It is non-ureolytic but studies have shown that that it has functional urease and can be activated though specific procedures.…”
Section: Bacillus Subtilismentioning
confidence: 99%
“…Bacillus subtilis is an aerobic, Gram-positive, spore forming, and rod-shaped bacterium commonly found in soil, water, and plants. It can produce various metabolites and has great potential in industrial applications [85][86][87][88]. It is non-ureolytic but studies have shown that that it has functional urease and can be activated though specific procedures.…”
Section: Bacillus Subtilismentioning
confidence: 99%
“…The carbon black and carbon nanotubes (CNTs) showed quite high conductivity compared to conventional carbon, but the bacterial cellular toxicity of these materials makes them unsuitable for BMFCs operation. The bacterial cellular toxicity and susceptibility towards oxidation dragged the interest towards the utilization of graphene derivatives [15]. Graphene derivatives are sp 2 hybridized carbon atoms which are organized in a honeycomb frame.…”
Section: Introductionmentioning
confidence: 99%
“…PEMFCs are the most commercialized and are used to generate without limits on placement, including in houses and buildings, transportation systems, and portable devices [ 2 , 3 ]. In addition, microbial fuel cells using proton exchange membranes have attracted attention for their improved performance owing to the development of anode materials [ 4 , 5 ]. Meanwhile, AEMFCs contain hydrocarbon polymer electrolyte membranes and are operated at low temperatures of ≤ 100 °C [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the electrode ionomer significantly influences catalyst layer morphology and fuel cell performance [ 4 , 5 , 20 , 21 ], e.g., the free volume of the polymer structure and the permeability of the electrode to gases can both be increased by using electrode ionomers highly permeable to fuels [ 20 , 21 ]. Choi et al studied the effect of spirobiindane units of bulky moieties in poly(ether sulfone)s, showing that the high gas permeability of the electrode binder contributes to AEMFC performance improvement [ 20 ], whereas Liang et al introduced an ionomer cross-linking immobilization strategy to realize efficient gas permeation and prevent the coalescence of Pt/C nanoparticles [ 21 ].…”
Section: Introductionmentioning
confidence: 99%